Gamma Delta TCR and the WC1 Co-Receptor Interactions in Response to Leptospira Using Imaging Flow Cytometry and STORM - Gillespie, Alexandria; Gervasi, Maria Gracia; Sathiyaseelan, Thillainayagam; Connelley, Timothy; Telfer, Janice C.; Baldwin, Cynthia L. (Frontiers in Immunology, 2021)
The WC1 cell surface family of molecules function as hybrid γ𝛿 TCR co-receptors, augmenting cellular responses when cross-linked with the TCR, and as pattern recognition receptors, binding pathogens. It is known that following activation, key tyrosines are phosphorylated in the intracytoplasmic domains of WC1 molecules and that the cells fail to respond when WC1 is knocked down or, as shown here, when physically separated from the TCR. Based on these results we hypothesized that the colocalization of WC1 and TCR will occur following cellular activation thereby allowing signaling to ensue. We evaluated the spatio-temporal dynamics of their interaction using imaging flow cytometry and stochastic optical reconstruction microscopy. We found that in quiescent γ𝛿 T cells both WC1 and TCR existed in separate and spatially stable protein domains (protein islands) but after activation using Leptospira, our model system, that they concatenated. The association between WC1 and TCR was close enough for fluorescence resonance energy transfer. Prior to concatenating with the WC1 co-receptor, γ𝛿 T cells had clustering of TCR-CD3 complexes and exclusion of CD45. γ𝛿 T cells may individually express more than one variant of the WC1 family of molecules and we found that individual WC1 variants are clustered in separate protein islands in quiescent cells. However, the islands containing different variants merged following cell activation and before merging with the TCR islands. While WC1 was previously shown to bind Leptospira in solution, here we showed that Leptospira bound WC1 proteins on the surface of γ𝛿 T cells and that this could be blocked by anti-WC1 antibodies. In conclusion, γ𝛿 TCR, WC1 and Leptospira interact directly on the γ𝛿 T cell surface, further supporting the role of WC1 in γ𝛿 T cell pathogen recognition and cellular activation.